Criticism Metaphors in the Legend of the Marriage Proposal to Puteri Gunung Ledang: A Pragmatic Analysis - Jalaluddin, Nor Hashimah; Osman, Maizura (Melayu: Jurnal Antarabangsa Dunia Melayu, 2018)
This study focuses on criticism of the King's attitude and leadership, as metaphorized by the traditional writers in the legend of Puteri Gunung Ledang. The analysis was conducted using a pragmatic approach, employing the ad hoc concept of the relevance theory,and supported by Bridging Cross Reference, whereas the data used were extracted from the Malay Annals (1997). The results of the study indicate that the legend of Puteri Gunung Ledang was created with the aim of conveying the people's criticisms of the King during that particular era. The true meaning of these metaphoric criticisms can only be discerned through a reasonable pragmatic analysis. The findings also reveal the reason why these criticisms were not made directly. Through this theoretical study, it can be concluded that the traditional Malay writers were intellectuals who incorporated important messages figuratively in myths and legends intertwined with history. Key words: metaphor, criticism, myth, relevance theory, pragmatic